The Concept Perspective of Karmaphala as The Law of Cause and Effect in The Pillars of Hindu Religious Beliefs - Pandeyana, I Ketut Mara; Oka Dharma, Ida Bagus Gede Raditya (International Journal of Multidisciplinary Sciences, 2024)
The teaching of Karmaphala is the arrangement of cause and effect in Hinduism. Karma (movement) is the cause, and Phala (result) is the effect. Karmaphala Ngaran Ika Phalaning Gawe Hala Hayu means that Karmaphala is the final result of good or bad deeds. This movement of existence is like a mill wheel, like the turning of a wheel that expects the second to be below and above, according to setting goals and collisions. Karmaphala is classified into three parts: Sancita Karmaphala, Prarabda Karmaphala, and Kriyamana Karmaphala. The literary sources end with the doctrine adopted by Hindus to navigate the sea of lifestyle. As new knowledge, it demands humans to make choices quickly. Thinking about how people behave is suggested to accommodate this. However, many are trapped by preferences to follow trends that forget the noble values of faith. This research technique was descriptive qualitative, using sources that could be applied to the research. This study aimed to determine the perspectives of the concept of Hinduism teachings, especially Karmaphala, as the law of reason and influence in the pillars of Hinduism.